Characterization of N and O-atoms, of N\(_2\)(A) and N\(_2\)(X,v>13) Metastable Molecules and N\(_2\)+ ion Densities in Ar-N\(_2\) Afterglows Plasmas from Microwave Discharges - Hayat Zerrouki; André Ricard; Jean-Philippe Sarrette (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The findings underscore the potential of N2(A) and N2+ species to enable sustainable and efficient surface treatments with applications ranging from medical devices to advanced material coatings. Afterglow jets of Ar-N2 flowing microwave discharges are characterized by optical emission spectroscopy. The N and O atoms, the N2(A) and N2(X,V>13) metastable molecules and N2+ ion densities are determined after calibration by NO titration for N and O-atoms and measurements of NO and N2 band intensities. For an Ar-xN2 gas mixture with x increasing from 2 to 100% at 4 Torr, 100 Watt and an afterglow time of 310-3 s at the 5-liter reactor inlet, it is found densities in the ranges of (2-6)1014cm-3 for N - atoms, one order of magnitude lower for N2(X,v>13) and for O - atoms (coming from air impurity), of 1010 - 1011 cm-3 for N2(A) and of 108 - 109cm-3 for N2+.